THE PARTICIPATION OF THE MUNICIPALITY OF UBERLANDIA (MG) IN THE TERRITORIAL DIVISION OF WORK IN THE CONTEXT OF AGRIBUSINESS - Oliveira, Denise Leonardo Custodio Machado de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The present study aims to analyze the participation of the municipality of Uberlandia (MG) in the territorial division of labor, through exporting of agricultural and agroindustrial products, starting in the year 2000. For this purpose, we closely analyze the insertion of Brazil in the international division of labor based on the evolution of exports volume, as well as in the exporting agenda of agribusiness, and, in this context, the participation of the State of Minas Gerais in the commodities trading. With this municipality being the focus of the analysis, the procedure adopted consists of the collection of data referring to exporting agenda related to the main countries of destination of exports, in the period from 2000 to 2014. Through (scientific) research, it was found that Uberlandia is coupled with the international sphere throughout exporting basics and semi-manufactured products, since soybean complex, meat and hides prevail in the exporting agenda, intended to several countries. Thus, it has become clear the participation/involvement of Uberlandia in the territorial division of labor and its articulation in the Global commodity trading, as well as a closer commercial relations with the Asian market, specially China.
Keywords: Uberlandia; Territorial division of labor; Commodities trading; Asian market; China